Intervenções contemporâneas em patrimônio edificado: obras do arquiteto Nelson Dupré - Jaccoud Junior, Eduardo Adalberto (2019)
This study seeks to examine the contemporary interventions adopted by architect Nelson Carlos Lauson Dupré, in built heritage in the city of São Paulo. The objective of this work is to analyze the projective postures from his following works: Brazilian Cinematheque - Old Slaughterhouse of Vila Mariana (1887) and the São Paulo Room at Júlio Prestes Station (1938). In the case studies presented will be analyzed the contemporary strategies adopted by the architect in the ambit of the preservation and conservation of the built heritage. The method used employs bibliographic surveys, analyzes and reflections regarding the theories, concepts, recommendations applied in interventions, such as: the preservation, conservation and restoration of built heritage demonstrated through the Heritage Letters and texts that contributed to the practice of heritage preservation. The other phases of the method refer to field surveys and consultation of the collection with the author of the projects. The results of this investigation may assist other research and projects in the area of interventions in overturned buildings.